Transforming Arabic Learning in Indonesian Pesantren: Policy, Teacher Competence, and Reform Challenges - Tauhid Tauhid (Universitas Muhammadiyah Sumatera Barat, 2026)
This study examines the transformation of Arabic language learning in Indonesian pesantren, conceptualized as a multidimensional process involving curriculum reform, pedagogical innovation, teacher professional development, institutional adaptation, and digital integration. The study aims to analyze the role of government policies, teacher competence, and reform challenges in supporting educational transformation. A qualitative Systematic Literature Review (SLR) using the PRISMA framework was conducted. Data were collected from peer-reviewed journal articles indexed in Scopus, Google Scholar, ERIC, and SINTA published between 2020 and 2025. Articles focusing on Arabic language learning, pesantren education, educational transformation, curriculum reform, and teacher competence were included, while conference proceedings, theses, dissertations, and irrelevant studies were excluded. Of 186 identified records, 42 articles met the eligibility criteria. The findings reveal that government policies have promoted curriculum flexibility, digitalization, and teacher professional development. However, transformation remains uneven, with larger and better-resourced pesantren demonstrating greater technological adaptation than smaller institutions. Major barriers include limited infrastructure, low digital literacy, and institutional resistance to change. This review is limited by the predominance of Indonesian-language publications and the scarcity of empirical field-based studies. The findings imply the need for equitable digital infrastructure, continuous teacher development, and context-sensitive policy implementation to support sustainable transformation in pesantren.